2023
DOI: 10.3126/jgmcn.v16i1.53428
|View full text |Cite
|
Sign up to set email alerts
|

Prevalence and factors influencing physical activity among secondary school adolescents: A cross-sectional study

Abstract: Introduction: Physical inactivity is a major health concern among adolescents and is an independent, modifiable risk factor for several non-communicable diseases. Despite the World Health Organization recommended physical activity levels, many adolescents do not meet these guidelines. This study was conducted among secondary school students in Palpa district of Nepal to assess their physical activity levels and associated factors. Methods: A modified version of the Physical Activity Questionnaire Adolescents w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(3 citation statements)
references
References 18 publications
0
3
0
Order By: Relevance
“…A cross-sectional study conducted in 2023 among 424 secondary school students in Nepal with the aim of assessing students' physical activity levels and factors associated with it revealed that only 25.31% of students were engaged in physical activity quite often or always whereas only 23.10% met the daily WHO recommendation of at least 60 minutes of physical activity per day. Moreover, females were less likely to achieve the recommended physical activity level compared with males (Nepal S et al, 2023).…”
Section: Literature Reviewmentioning
confidence: 95%
See 2 more Smart Citations
“…A cross-sectional study conducted in 2023 among 424 secondary school students in Nepal with the aim of assessing students' physical activity levels and factors associated with it revealed that only 25.31% of students were engaged in physical activity quite often or always whereas only 23.10% met the daily WHO recommendation of at least 60 minutes of physical activity per day. Moreover, females were less likely to achieve the recommended physical activity level compared with males (Nepal S et al, 2023).…”
Section: Literature Reviewmentioning
confidence: 95%
“…Several studies have pointed out a decline in physical activity among adolescent and youths upon enrolling to university life, which is on the rising trend (Kumar SP et al, 2021;Kljajevic, V et al, 2022;Kumar K et al, 2022). Academic workload, lack of break time, poor access to sports facilities and increasing indulgence/engagement of adolescents and youths in sedentary activities such as use of cell phone and social media as well as the lack of self-discipline and laziness towards maintaining healthy behavior towards personal care might be the likely reasons for such decline, which negatively affects their health and wellbeing (Chaabna K et al, 2022;Thariyan P et al, 2023;Oladejo T et al, 2023;Nepal S et al, 2023;Pate RR et al, 2006). Moreover, studies done among school and university students have indicated likely correlation between physical activity and academic performances whereas physical inactivity likely exerting deleterious effect on academic performances (Hariyanto A et el., 2023;James J et al, 2023;Zhai X et al, 2022).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation